Penyuluhan dan Edukasi Senam Ergonomik untuk Mengatasi Masalah Asam Urat pada Lansia di Desa Cemani, Kecamatan Grogol Kabupaten Sukoharjo - Wahyudi, Didik; Widyastuti, Endang; Nawang, Pungky; Hidayatullah, Rafi Fuzan; Septiani, Risma Dyah; Purwandani, Safitri; Putri, Sheli Feliyan (Jurnal Pengabdian Arumbai, 2024)
High uric acid levels cause pain and swelling in the bones and joints, which are commonly experienced by most elderly individuals. Another factor that can increase uric acid levels is the excessive consumption of foods high in purines. Non-pharmacological treatment can be used to control uric acid levels, one of which is by performing ergonomic exercises. Ergonomic exercises involve muscle movements combined with breathing techniques. The purpose of this community service program is to enhance the elderly's knowledge of managing uric acid levels through ergonomic exercise training. The activities include delivering educational material, conducting ergonomic exercise training, as well as discussions and Q&A sessions. The results of this community service activity indicate that the elderly understood the material presented. Through presentations and ergonomic exercise demonstrations, there was a 22% increase in understanding, and they were able to perform ergonomic exercises independently.